An Empirical Investigation of Cost-Return Analysis of Roadside Marketing along Major Highways in Osun State, Nigeria - Adetayo, Adelu O.; Oloke, Emmanuel; Adegun, Emmanuel Aderinola; Olasupo, Sunday Festus; Aderemi, Timothy Ayomitunde (The Journal of Accounting and Management, 2022)
Roadside marketing is a prominent venture in Nigeria and its economic implications on the Nigerian populace cannot be ignored. Against this backdrop, the study examined the economics of roadside marketing of agricultural produce along major highways in Osun State. It described the socioeconomic features of the roadside marketers and also evaluated the associated costs and returns. The study utilized a two-stage sampling procedure to achieve its objectives. Consequently, four different highways (Ife-Ibadan expressway, Ilesha-Akure expressway, Osogbo-Gbongan expressway and Osogbo-Offa expressway) were purposively selected in the first stage. In the second stage, thirty five (35) respondents were selected in each of the four different locations using accidental sampling method. Primary data were then collected using pre-tested interview schedule administered to a total of one hundred and forty (140) roadside marketers. Descriptive statistics and Cost-Revenue Ratio (CRR) was used to analyze the data collected. Findings revealed that majority of the roadside marketers (85.7%) were less than 50 years of age, married (87.9%), had not less than a primary school education (85%), and had fewer than 10 years of marketing experience (56.4%). It was also revealed that the cost of setting up roadside marketing business is very low and that the net profit of roadside marketers around ₦23,039.00 per month. In view of the above these findings, this study recommends that roadside marketing is a profitable venture that should be explored and modernized in order to increase economic activities of the Nigerian highways.